ANALYSIS OF CARBOHYDRATE CONTENT IN VARIOUS TYPES OF FOOD - Nadila Sabrina; Khalsani Mutia Nadia Husna Kembaren (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Carbohydrates are one of the macronutrients that are essential for human life. Along with protein and fat, carbohydrates play a key role as the body's primary energy source. This study used qualitative methods. The study was conducted in the PGSD VI D class, room 206, STKIP Al Maksum Langkat. The results showed that high carbohydrates are found in foods that are the primary source of energy. Foods such as rice, bread, and bananas are high sources of carbohydrates. Foods such as eggs, fish, chicken, and cheese contain almost no carbohydrates. Fermented plant products such as tofu have a moderate carbohydrate content. Green vegetables have very low carbohydrate levels. Cassava leaves and kale are low in carbohydrates. These vegetables serve more as sources of fiber, vitamins, and minerals, rather than as a primary source of energy.